Exponential interpolation - Lee, Horng-shiou; Radok, Rainer; Vilas Wuwongse; Huynh, Ngoc Phien; R.O.C. Government (Bangkok : Asian Institute of Technology, 1985)
A method is developed and tested for the interpolation of equally and unequally observational data by means of sums of exponentials with unknown coefficients and exponents.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1985
Keywords: Interpolation